Death Penalty and Rights of Inmates on The Death Row under Indonesia Criminal Justice System - Zenny Rezania Dewantary (Problematika Hukum, 2018)
Indonesia has executed approximately 84 inmates in the death row since 1998. Indonesia actively performed death execution until 2016. After 2016, although no execution has been done, there was a death penalty dropped in 2018. In relation to that, death penalty is stipulated in Indonesia Criminal Code (KUHP and other penal codes outside KUHP) and this makes Indonesia as a retentionist country. Death penalty delivers a death row. Death row is a prolonged death execution, which usualy measured in years. This situation caused a double-punishment, where the convicted must serve in an isolation room in prison, while waiting to be executed. This waiting period seems unavoidable due to some factors. Using normative-empirical research method, this research aims to bring the fact that in Indonesia, there are several factors that have been causing a death row. In this research, this situation is tested using state responsibility principle and some international conventions Indonesia has ratified. The absence of provision related to maximum death execution time after verdict is binding without further objections, together with the hierarchical system of court trial in Indonesia is the cause factor for the prolonged death execution. To encounter this situation The Government of Indonesia is proposed to (1) for short term goal, regulate strictly about the implementation of death execution; (2) for long term goal, to abolish capital punishment from the justice system.